Evolving OpenMP in an Age of Extreme Parallelism 5th International Workshop on OpenMP, IWOMP 2009 Dresden, Germany, June 3-5, 2009 Proceedings - M<U+00fc>ller, Matthias S.; Supinski, Bronis R.; Chapman, Barbara M. (Lecture Notes in Computer Science, 2009)
This book constitutes the refereed proceedings of the 5th International Workshop on OpenMP, IWOMP 2009, held in Dresden, Germany in June 2009. The papers are organized in topical sections on performance and applications, runtime environments, tools and benchmarks as well as proposed extensions to OpenMP.